Bumpy Road: The Making, Flop, and Revival of Two-Lane Blacktop - Townsend, Sylvia (University Press of Mississippi, 2019)
Bumpy Road: The Making, Flop, and Revival of ""Two-Lane Blacktop"" chronicles the genesis, production, box-office debacle, resurrection, near-canonization, and lasting influence of director Monte Hellman's 1971 existentialist car-racing movie. Hellman's unconventional choices for the film included casting three nonactors-musicians James Taylor and Dennis Wilson, as well as his girlfriend, Laurie Bird-in lead roles; shooting the movie in sequence from west to east on Route 66; and refusing to show the actors the full script, instead giving each his or her lines for the day. -- -- Before its release, Esquire put the film on its cover as the magazine's choice for movie of the year and printed the entire screenplay, leading moviegoers to expect a crowd-pleaser. Audiences anticipated that Two-Lane Blacktop would be an action-packed car-racing movie and were disappointed when nobody won or even finished the race, no one got the girl, the two leading men barely spoke, and the leading lady was foul-mouthed and promiscuous. Universal Studios Chairman Lew Wasserman found the film subversive and refused to release it on video. -- -- Years after it flopped, however, the movie soared in stature, and it is now revered by such contemporary directors as Quentin Tarantino and Richard Linklater, was honored with inclusion in the National Film Registry and was released on DVD and Blu-ray by the prestigious Criterion Collection and the highly regarded Masters of Cinema series. -- -- Author Sylvia Townsend conducts a comprehensive examination of the film, its reception, and the resurgence of interest it has more recently generated. Interviewing individuals involved in and influenced by the film, including James Taylor, Richard Linklater, Gary Kurtz, and scriptwriter Rudy Wurlitzer, Townsend provides an inside look at the cult classic.
https://katalog.adlr.link/Record/51-9781496804143